2018
DOI: 10.1155/2018/1027152
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation and Acute-on-Chronic Liver Failure: Too Much, Not Enough

Abstract: ACLF is a specific, but complex and multifactorial form of acute decompensation of cirrhosis and is characterized by an extraordinary dynamic natural course, rapidly evolving organ failure, and high short-term mortality. Dysbalanced immune function is central to its pathogenesis and outcome with an initial excessive systemic inflammatory response that drives organ failure and mortality. Later in its course, immuno-exhaustion/immunoparalysis prevails predisposing the patient to secondary infectious events and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 81 publications
2
57
0
1
Order By: Relevance
“…Although advanced chronic liver disease features systemic inflammation, "sepsis-like" immune paralysis develops in more severe stages facilitating secondary infections and organ failure (37,38). Mincle possibly plays an important role in these apparently opposing observations, since the dysregulation of mincle signaling in spleen and PBMC, as important compartments of the immune system, could be responsible for the failure to clear invading gut bacteria and consequent systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although advanced chronic liver disease features systemic inflammation, "sepsis-like" immune paralysis develops in more severe stages facilitating secondary infections and organ failure (37,38). Mincle possibly plays an important role in these apparently opposing observations, since the dysregulation of mincle signaling in spleen and PBMC, as important compartments of the immune system, could be responsible for the failure to clear invading gut bacteria and consequent systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the established prognostic scores that based on conventional clinical parameters, biomarkers related to inflammation and immune for early prediction of HBV‐ACLF are also being explored . Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the established prognostic scores that based on conventional clinical parameters, biomarkers related to inflammation and immune for early prediction of HBV-ACLF are also being explored. 28 Zhang et al report that frequency of Th17 cells predicts 3-month prognosis equivalent to MELD and CLIF-C ACLF scores in HBV-ACLF. 29 Similarly, our current study showed that serum NMI may have prognostic value equivalent to MELD and CLIF-C ACLFs in predicting 3-month mortality in HBV-ACLF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired dysfunctional immunity in cirrhosis predisposes patients to frequent bacterial infections contributing to disease progression and may lead to the development of acute-onchronic liver failure (ACLF) (1). Especially, spontaneous bacterial peritonitis (SBP) is one of the most frequent infections in cirrhosis and therefore a trigger for ACLF (2).…”
Section: Introductionmentioning
confidence: 99%